2020
DOI: 10.3390/app10155244
|View full text |Cite
|
Sign up to set email alerts
|

A Theoretical Method for Evaluating the Lubrication Performance of the Meshing Pair Profiles in Water Flooded Single Screw Compressors Based on the Micro Deflecting Motion Trajectory

Abstract: To improve the life of the meshing pair in single screw compressor (SSC), several meshing pair profiles (MPP) were proposed for raising the lubrication properties. Therefore, it is necessary to evaluate the lubrication performance of the MPPs. In this paper, an evaluation method based on micro deflecting motion trajectory (MDMT) is proposed and the theoretical model to realize MDMT is established. The model mainly contains a geometric model, a thermodynamics model, a hydrodynamic lubrication model and correspo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Studies on WLSSAC performance remain limited. Li et al examined the impacts of different meshing pair lines on a single-screw compressor's hydrodynamic lubrication parameters using both theoretical and experimental approaches and determined that an optimal impact of water lubrication can be obtained using the multiple cylindrical meshing pair [12][13][14][15]. Yet, there has to date been no study on the impact of water injected parameters on compressor performance.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on WLSSAC performance remain limited. Li et al examined the impacts of different meshing pair lines on a single-screw compressor's hydrodynamic lubrication parameters using both theoretical and experimental approaches and determined that an optimal impact of water lubrication can be obtained using the multiple cylindrical meshing pair [12][13][14][15]. Yet, there has to date been no study on the impact of water injected parameters on compressor performance.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the authors proposed an evaluation criterion for the envelope profile. Li et al 5,18,19 carried out experimental and theoretical research on lubrication characteristics of the meshing pair with single-line, single-column and multicolumn envelope profiles. The authors demonstrated the accuracy of the "double-sided slider" model.…”
Section: Introductionmentioning
confidence: 99%